PENGARUH KEPEMIMPINAN, MOTIVASI BERPRESTASI, KOMITMENAFEKTIF DAN STRESS KERJA TERHADAPKINERJATENAGA PENJUAL (SALESMAN)MOTOR SUZUKI DI AREA PURWOKERTO SEKITARNYA - Rizza Adi Putra; Hengky Widhiandono (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2015)
The research was aimed at reveal the influence of leadership, motivation to excel, affective commitment and stress at work partially and simultaneously to word Suzuki salesmen’s performance in Purwokerto and the surrounding area. The type of this study is survey research. The subjects were 83 Suzuki salesmen in Purwokerto and the surrounding area, with more than one year working experience. There are 59 people participate as the respondents. The researcher employs multiple regressions to analyze the data. The findings show that partially, the factors like leadership, motivation to excel, affective commitment and stress at work influence Suzuki salesmen’s performance in Purwokerto and the nearby area simultaneously, there is influence of leadership, achievement motivation, affective commitment and stress at work toward Suzuki salesmen’s performance in Purwokerto and the surrounding area. Keywords: leadership, achievement motivation, affective commitment, stress at work, toward Suzuki salesmen’s performance.